A predictive nomogram to identify factors influencing the success of a concomitant laparoscopic cholecystectomy with common bile duct exploration for choledocholithiasis. Issue 4 (April 2018) - Chue, Koy Min; Aw, Jun Wei Bryan; Chua, Sin Hui Melissa; Chen, Zhaojin; Iyer, Shridhar Ganpathi; Madhavan, Krishnakumar; Kow, Alfred Wei Chieh
Abstract: Background: Single-staged laparoscopic common bile duct exploration (LCBDE) offers clear benefits in terms of cost and shorter hospitalization stays. However, a failed LCBDE requiring conversion to open surgery is associated with increased morbidity. This study reviewed the factors determining success of LCBDE, and created a predictive nomogram to stratify patients for the procedure. Methods: A retrospective analysis of 109 patients who underwent LCBDE was performed. A nomogram was developed from factors significantly associated with conversion to open surgery and validated. Results: Sixty-two patients underwent a successful LCBDE, while 47 patients required a conversion to open CBDE. The presence of underlying cholangitis (crude OR 2.70, 95% CI: 1.12–6.56, p = 0.017), together with its subsequent interventions, seemed to adversely increase the rate of conversion to open surgery. The predictive factors included in the nomogram for a failed laparoscopic CBDE included prior antibiotic use (adjusted OR (AOR) 2.98, 95% CI: 1.17–7.57, p = 0.022), previous ERCP (AOR 4.99, 95% CI: 2.02–12.36, p = 0.001) and abnormal biliary anatomy (AOR 9.37, 95% CI: 2.18–40.20, p = 0.003). Conclusion: LCBDE is useful for the treatment of choledocholithiasis. However, patients who were predicted to have an elevated risk for open conversion might not be ideal candidates for the procedure.